Magang Bersertifikat di Kantor Akuntan Publik Basyiruddin dan Rekan - Handini Rahmadani; Syawwa Alfina Amelia (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The increasing number of graduated students in universities has also resulted in high competition in job search. To overcome this problem, the Minister of Education and Culture, Nadiem Makarim made one of the new policies, namely Merdeka Belajar–Kampus Merdeka (MBKM). Universitas Islam